1997
DOI: 10.1063/1.474226
|View full text |Cite
|
Sign up to set email alerts
|

Highly excited vibrational states of HCP and their analysis in terms of periodic orbits: The genesis of saddle-node states and their spectroscopic signature

Abstract: We present quantum mechanical bound-state calculations for HCP(X) using an ab initio potential energy surface. The wave functions of the first 700 states, corresponding to energies roughly 23 000 cm Ϫ1 above the ground vibrational state, are visually inspected and it is found that the majority can be uniquely assigned by three quantum numbers. The energy spectrum is governed, from the lowest excited states up to very high states, by a pronounced Fermi resonance between the CP stretching and the HCP bending mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 44 publications
9
64
0
Order By: Relevance
“…64,65 Inspired by this prediction, Ishikawa et al 40 have searched for these states and indeed found a series of states, which could not be assigned in the way the other levels were assigned. Moreover, these states showed a large anharmonicity and had unusually large rotational B 0 constants, just the criteria typical for the isomerization states.…”
Section: Quantum Mechanical Point Of View: the Genesis Of "Isomermentioning
confidence: 99%
“…64,65 Inspired by this prediction, Ishikawa et al 40 have searched for these states and indeed found a series of states, which could not be assigned in the way the other levels were assigned. Moreover, these states showed a large anharmonicity and had unusually large rotational B 0 constants, just the criteria typical for the isomerization states.…”
Section: Quantum Mechanical Point Of View: the Genesis Of "Isomermentioning
confidence: 99%
“…Such a qualitative change in the vibrational character had been predicted in a theoretical study carried out by Schinke and co-workers (10,11). Our analysis has been restricted to deal exclusively with the interaction between the bend and CP stretch modes, since there had been no experimental observations of highly excited vibrational levels with v CH 0.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, the HCP 7 CPH isomerization reaction in the high-energy region in the X 1 ⌺ ϩ state has been extensively studied experimentally (6 -9) and theoretically (10,11) recently. To observe highly excited vibrational levels in the X 1 ⌺ ϩ state, dispersed fluorescence (DF) and stimulated emission pumping (SEP) spectroscopies are very useful, since excited electronic states have a bent configuration, whereas the X state is linear.…”
Section: Introductionmentioning
confidence: 99%
“…In two previous publications [4,5] we have presented a detailed classical and quantum mechanical study of its vibrational motion up to an energy range of about 3 eV above the minimum of the potential.…”
Section: Introductionmentioning
confidence: 99%